IMPLEMENTATION AND ACCOUNTABILITY OF VILLAGE FUND ALLOCATION MANAGEMENT BASED ON REGULATION OF THE MINISTRY OF HOME AFFAIRS NUMBER 113 OF 2014: (Case Study in Jugo Village, Kesamben Sub-District, Blitar Regency) - Rizky Dharmawan; Diana Elvianita Martanti (JOSAR (Journal of Students Academic Research), 2020)
The aims of this research is provides an overview of the Implementation of Village Fund Allocation (ADD) in Jugo village, Kesamben sub-district, Blitar district. Describing the Accountability of Village Fund Allocation Management (ADD) in 2019 in Jugo village, Kesamben sub-district, Blitar Regency. This research uses qualitative research with a descriptive approach. Qualitative descriptive research is to describe the respondent's opinion based on the research question, then analyzed with the words behind the respondent's behavior, reduced, triangulated, concluded, and verified. The results showed that the implementation of the Village Fund Allocation policy in Jugo Village, Kesamben Sub-District, Blitar Regency has been running according to the RKP but it has not run optimally according to Permendagri No. 113 & 114 of 2014. Based on Permendagri No. 113 & 114 of 2014, in general the management of the Village Fund Allocation is accountable and transparent at the stages of planning, implementation, administration, reporting, accountability and supervision. Supported by the community who participates active in deliberations to supervise village development.